2007
DOI: 10.1080/10556790701300603
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of EM Cep

Abstract: The UBVR photoelectric observations of the variable star EM Cep were made at the Abastumani Astrophysical Observatory, Georgia. On 15-16 November 1991 an unusual flare of this star was revealed. On 17-18 July 2003, flare activity of EM Cep was detected by Turkish astronomers. A suggestion as to the λ Eri-type variability of the star is made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Further observations showed the light variability to be quite irregular (Johnston 1970, Rachkovskaia 1975, 1976, Bakos & Tremko 1975. Flare events in the R band were also observed (Kochiashvili 1999, Kochiashvili et al 2007, Mars et al 2010). Molik & Wolf (2004) found that EM Cep falls on the "blue envelope" of the colour-period diagram of close binaries.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Further observations showed the light variability to be quite irregular (Johnston 1970, Rachkovskaia 1975, 1976, Bakos & Tremko 1975. Flare events in the R band were also observed (Kochiashvili 1999, Kochiashvili et al 2007, Mars et al 2010). Molik & Wolf (2004) found that EM Cep falls on the "blue envelope" of the colour-period diagram of close binaries.…”
mentioning
confidence: 91%
“…Different explanations have been proposed for this peculiarity: (a) an unstable common envelope around the components of the contact binary (Johnston 1970, Bakos & Tremko 1975, Rachkovskaia 1977, Briot 1986); (b) a magnetic, oblique rotator combined with a non-uniform brightness distribution over the stellar surface (Harmanec 1984, Balona 1990); (c) pulsations of β Cep or non-radial type (Rachkovskaia 1976, Hilditch et al 1982. Kochiashvili et al (2007) suggested that the star reveals λ Eri-type variability. Finally, we note that Pribulla & Rucinski (2006) found no observational confirmation of a third companion of EM Cep.…”
mentioning
confidence: 99%